2009
DOI: 10.1111/j.1745-4581.2009.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

RAPID DETECTION OF LISTERIA MONOCYTOGENES IN GROUND TURKEY BY IMMUNOMAGNETIC SEPARATION AND POLYMERASE CHAIN REACTION

Abstract: The aim of this study was to determine the prevalence of Listeria monocytogenes in packaged fresh ground turkey in Turkey using immunomagnetic separation (IMS) as a selective enrichment step in method and polymerase chain reaction (PCR). A total of 180 ground turkey samples were collected during a 1‐year period. Thirty‐two (17.7%) of the samples contained L. monocytogenes, 24 (13.3%) contained Listeria innocua, 7 (3.8%) had Listeria ivanovii and 5 (2.7%) had Listeria seeligeri by means of IMS‐based cultivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This is in agreement with the winter season findings of Elmali et al (2015). In a study by Ayaz and Erol (2009) where L. monocytogenes presence was investigated in turkey meats, it was reported that seasonal effect was not present due to the psychrotrophic character of the bacteria.`…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the winter season findings of Elmali et al (2015). In a study by Ayaz and Erol (2009) where L. monocytogenes presence was investigated in turkey meats, it was reported that seasonal effect was not present due to the psychrotrophic character of the bacteria.`…”
Section: Discussionsupporting
confidence: 90%
“…After assessing all the information from the recovered publications, seventy-eight primary studies [6,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,…”
Section: Methodsmentioning
confidence: 99%
“…It has been stated that poultry meat is more favorable for L. monocytogenes to reproduce than other meats [7]. There are several studies indicated that chicken and turkey meat are signifi cant sources of L. monocytogenes and the most common serotypes are 1/2a, 1/2b, 1/2c and 4b [16][17][18][19][20][21][22].…”
Section: Signifi Cance Of Listeria Monocytogenes As a Foodborne Pathogenmentioning
confidence: 99%